2008
DOI: 10.3748/wjg.14.5707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anatomical position on esophageal transit time: A biomagnetic diagnostic technique

Abstract: AIM:To study the esophageal transit time (ETT) and compare its mean value among three anatomical inclinations of the body; and to analyze the correlation of ETT to body mass index (BMI). M E T H O D S :A b i o m a g n e t i c t e c h n i q u e w a s implemented to perform this study: (1) The transit t i m e o f a m a g n e t i c m a r k e r ( M M ) t h r o u g h t h e esophagus was measured using two fluxgate sensors placed over the chest of 14 healthy subjects; (2) the ETT was assessed in three anatomical pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Research has demonstrated how specific postures can be used to compensate for particular types of dysphagia (e.g., delayed initiation of swallow, poor tongue control, unilateral pharyngeal paralysis, or unilateral paralysis of oral cavity and pharynx) by altering the way the bolus travels through the pharynx [8][9][10][11]. These techniques utilize the effect of gravity and altered body position to alter the internal structures and/or their response to a bolus traveling through the oropharyngeal cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated how specific postures can be used to compensate for particular types of dysphagia (e.g., delayed initiation of swallow, poor tongue control, unilateral pharyngeal paralysis, or unilateral paralysis of oral cavity and pharynx) by altering the way the bolus travels through the pharynx [8][9][10][11]. These techniques utilize the effect of gravity and altered body position to alter the internal structures and/or their response to a bolus traveling through the oropharyngeal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the pharyngeal bolus was not affected by gravity. Esophageal transit time has been found to be affected by gravity, resulting in a significantly faster transit time while in the upright position than in the supine [10]. With the exception of two reports [7,10], studies in this area have had between five and nine subjects.…”
Section: Introductionmentioning
confidence: 98%
“…At room temperature, the fixed mucosal intestinal tissue was continuously flushed with simulated fed-state fluid at 850 mL min −1 . The flow rate was selected based on the range of transit times for fluids in the GI tract; with the intestinal transit time for fed-state being approximately 2–3 mL min −1[41] and the esophageal transit time being around 700–800 mL min −1 , [42,43] a value near the upper boundary was selected to simulate the maximal physiological stress. The simulated fluid consisted of fed-state simulated intestinal fluid (FeSSIF, pH ~ 6.8) and EnsurePlus (pH ~ 6.6) in a ratio of 1:4 with foodstuffs (15 g L −1 of bread pieces and 50 g L −1 of rice) mixed in.…”
Section: Methodsmentioning
confidence: 99%
“…The esophageal transit time has also been evaluated. Techniques and instrumentation for biomagnetic studies permit the noninvasive functional evaluation of the gastrointestinal tract (Daghastanlietal., 1998;Córdova-Fraga et al, 2008).…”
Section: Magnetogastrographymentioning
confidence: 99%